Kesiapan Generasi Milenial Sebagai Role Model di Era New Normal - Riesty Amaylia Safitri (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2022)
In 2020, the year the demographic bonus begins, the millennial generation is in the age range of 20 years to 40 years. This age is a productive age which is predicted to be the backbone of Indonesia's change. However, before achieving the optimization of the demographic bonus which is considered to have a positive impact, Indonesia was first hit by the Covid-19 outbreak with a very fast transmission. Not wanting to linger in uncertainty when the pandemic will end, the Government finally decided to live side by side with Cov19, one of which was by issuing a New Normal policy with the aim of keeping people productive and safe from Covid-19 during the pandemic. Therefore, the community needs a role model that can be used as an ideal role model and example. The millennial generation with all the characteristics and skills they have in this phase is seen as being able to become a role model in facing rapid changes and new orders in society. The approach used is a qualitative approach using literature study methods from books, journals and other sources relevant to the title. The result of this paper is that the productive age of the millennial generation has been in the take off phase, meaning that it can be used as a role model by the community.